Antibacterial and antibiofilm activity of carvacrol against Salmonella enterica serotype Typhimurium - Daliah Alves Coelho Trevisan; Alex Fiori da Silva; Melyssa Negri; Benício Alves de Abreu Filho; Miguel Machinski Junior; Eliana Valéria Patussi; Paula Aline Zanetti Campanerut-Sá; Jane Martha Graton Mikcha (Brazilian Journal of Pharmaceutical Sciences, 2018)
ABSTRACT The present study evaluated the antibacterial and antibiofilm activity of carvacrol against Salmonella Typhimurium. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined and the time-kill curve and scanning electron microscopy (SEM) were performed to evaluate antibacterial activity. Antibiofilm activity was evaluated by quantifying total biomass using crystal violet assay, and metabolic activity was determined using MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. The action of carvacrol against preformed biofilm on polypropylene and stainless steel was also evaluated by colony counting and SEM. The MIC and MBC was 312 µg mL-1. Carvacrol at MIC and 2 x MIC eliminated cells after 6 and 1 h of treatment, respectively, as exhibited in the time-kill curve. The greatest reduction in biofilm biomass and metabolic activity was 1,719 OD550 and 0,089 OD550 respectively, both at 4 x MIC of carvacrol. In carvacrol treated biofilms of S. Typhimurium on polypropylene, a reduction of 5.12 log was observed with 4 x MIC, while on stainless steel, carvacrol at 4 x MIC reduced bacterial counts by 5 log. The results showed that carvacrol exhibits antibacterial activity and can be used as an alternative for the control of S. Typhimurium biofilms.